Investigating the magnetic properties of tissue with MRI phase at 7T - Tendler, Benjamin Charles (2017)
In this thesis, the potential of MRI phase to reveal the magnetic properties of tissue is thoroughly investigated. Extending beyond the well established field of quantitative susceptibility mapping (QSM), consideration is given to the influence of susceptibility anisotropy, chemical exchange, non-spherical susceptibility inclusions and multi-compartmental signal evolution from both a theoretical and experimental viewpoint. The first experimental chapter discusses a collaborative project with Cardiff University Brain Research Imaging Centre (CUBRIC) and the Department of Neurobiology in Tel-Aviv University to investigate neuroplasticity changes in rats. In this chapter the contribution from the SPMIC is described, detailing an analysis pipeline to generate and optimise isotropic susceptibility and R2∗ maps from multi-echo gradient echo (GE) in-vivo rat datasets obtained on a 7T Bruker Biospec 70/30 MR system. The second experimental chapter investigates the potential of frequency difference mapping (FDM), a recently developed phase processing technique which characterises multi-compartmental signal evolution to probe microstructure content. In this chapter, a novel FDM processing algorithm is introduced which does not require the use of sophisticated phase unwrapping and image filtering. To test the effectiveness of the FDM algorithm on experimental data, ten healthy volunteers underwent a single-slice, sagittal, multi-echo GE scan on a Philips Achieva 7T MR system. Results revealed consistent contrast over the corpus callosum relative to the surrounding tissue and a high sensitivity to small changes in microstructure content. Though fitting experimental magnitude and frequency difference evolution to a three-pool white matter model, the signal evolution over the corpus callosum is described in terms of physical properties of the nerve fibres. The final experimental chapter investigates the magnetic properties of skeletal muscle. A skeletal muscle sample (in the form of a section of pork tenderloin) was placed within an agar phantom and scanned via a multi-orientation, dual-echo GE protocol on a Philips Achieva 7T MR system. Measured phase data were post-processed and novel least-squares minimisation algorithms were developed to investigate the isotropic susceptibility, anisotropic susceptibility, chemical exchange and cylindrical microstructure inclusion properties of the sample. Analysis revealed that the skeletal muscle sample was significantly more diamagnetic than agar, χI = (−121 ± 22)ppb, and a large chemical exchange contribution was also observed within the tissue, E = (31 ± 11)ppb, relative to the surrounding agar. The experimental protocol was not sensitive enough to reveal quantitative information about the anisotropic susceptibility properties of the sample, yielding an an upper bound of 10 ppb. No evidence of cylindrical susceptibility inclusions was observed within the experimental field perturbation maps.